Efektivitas Akses Layanan Pendidikan Melalui Program Indonesia Pintar Peserta Didik Generasi Z - Ana Setiyaningrum Ana; Toni Harsan; Siti Fatimah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Facing global competition and maximizing the process of forming advanced and superior Human Resources (HR) requires means through education. The 12-year compulsory education program from the Government is to prepare for the golden generation of 2045. The purpose of this research is to find out how effective access to education services is through the Smart Indonesia program for Generation Z students. The research method uses qualitative methods with a descriptive approach. To measure the effectiveness of the Smart Indonesia program, the theory fromKettner, Moroney, and Martin.The results showed that the utilization of aid funds for the smart Indonesia program was going well and students used according to government procedures where they only bought school equipment and needs with satisfactory quality because students took part in competitions both in the non-academic (art sports) and academic fields.Thus, in the future students will continue to increase their potential to become superior and achievers.